Changing Urban Housing Pattern of Ahmedabad: A Study of Indian Knowledge System and Sociological Perspective - Mayank K. Patel; Dr. Amarjeet Kumar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The geographical location of Ahmedabad is 23.03°N 72.58°E and is the fifth most populated city of India. The city has a population of 5,633,927 as per 2011 population census. It is located on the banks of the Sabarmati River. Political authorities and affluent merchants deliberately founded the walled city of Ahmedabad. The Pol houses are situated in the walled city of Ahmedabad. UNESCO declared the walled city of Ahmedabad as Heritage city in 2017. The present Pol houses are similar to rural houses of Gujarat but identify themselves as Pol houses in the walled city of Ahmedabad only. Locals design the houses, and these houses share the same principles of design throughout the walled city of Ahmedabad. In 1990 the new economic policy of modernisation had led to proliferation. Economic integration causing global norms, ideas, and practices to dilute local cultures. Apartments or contemporary houses without a courtyard have replaced local traditional architecture as these can fit anywhere irrespective of climate, social, cultural background. Due to an increase in population and less land availability, it is collective thinking that high rise high-density apartments are required, which leads to no need for local traditional residential architecture. Ahmedabad residential market saw 3 BHK apartments constitute a notable 47 percent of the total units sold in Q3 2023. In modern times we take the help of the professionals who can build a good house with a solid foundation, strong walls, a proper structural balance with the right weight and pressure distribution, proper plumbing, electricity, air light etc. This branch of modern knowledge is called architecture, or civil engineering. The ancient seers of India knew not only the above, but quite a few other things beyond. Hence their house building principles included: the North-South flow of magnetic forces: the East-West earth motion and Solar energy forces: and with Divine Spiritual Perception, they also knew the various Deities who rule the different sections of the house and based on the Nature of the Deities, what type of room/function is ideal in that part of the house. This branch of ancient Indian knowledge is called Vastu Sastra, or Vastu Shilpa sastra, or Vastu Nirmana sastra. It was employed to build not just houses but to plan and build entire towns and cities and temples.
Keywords: Vernacular; Traditional; Vastu shastra; Pol houses; Apartments; High rise